DEVELOPMENT OF DISCUSSION SKILLS FOR PRIMARY TEACHERS IN TRAINING STUDENTS AT ENGLISH CLASSES - Opincane, Marite (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The development of discussion skills is one of the most essential aims in the acquisition of foreign languages. Discussion skills are essential both for students in study process and for teachers in their professional work. The objective of the research is to investigate the improvement and perfection of discussion skills as well as motivate students to participate in discussions using the structured discussions, perfecting the discussions skills and acquiring the ESP vocabulary. Every discussion has to be purposeful and well-structured. The university lecturers have to perfect the skills of discussion planning, management and analysis. The results acquired proved that students’ discussion and listening skills, as well as the knowledge of ESP vocabulary increased. However, some other language skills, particularly the fluency that is based on the knowledge of the language structures did not improve considerably.